TOTAL INCLUSION IN DEMOCRACY AS A PROBLEM OF POLITICAL DEVELOPMENT - Tymchyshyn, B. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Having defeated global socialism in the competition, liberalism and democracy proved their superiority. Having freed themselves from obvious external threats, domestic political challenges began to acquire increasing importance. Internal factors mean both the problems of each particular democratic society and the problems of conceptual understanding of liberal democracy in the contemporary context.It turns out that populism in the last 5 years has become the most dangerous problem in a number of young and mature democracies. The populist rhetoric of politicians is aimed at the part of the electorate that is ignorant and eager to hear quick solutions to complex systemic problems. This is especially dangerous for societies in which a political nation has not yet been formed, which is just beginning to take its first steps towards its own institutionalization and therefore requires the attention and concrete action of responsible civil society.Exacerbations of the chronic problems of society remain unnoticed by many influential politicians.  The problem of developing complex solutions to the new challenges of our time, in particular the need to understand what price society pays for the dogmatic faith in the permanent liberalization of the democratic process and the inclusion of various groups, is being solved. The necessity of adapting the structures of liberal democracy to the new conditions of the prevailing modern political reality in order to maintain political security is noted. A proposal is made to look pragmatically at the state of affairs of modern liberalism.